2021
DOI: 10.14218/jcth.2021.00062
|View full text |Cite
|
Sign up to set email alerts
|

HBV Integration Induces Complex Interactions between Host and Viral Genomic Functions at the Insertion Site

Abstract: Hepatitis B virus (HBV), one of the well-known DNA oncogenic viruses, is the leading cause of hepatocellular carcinoma (HCC). In infected hepatocytes, HBV DNA can be integrated into the host genome through an insertional mutagenesis process inducing tumorigenesis. Dissection of the genomic features surrounding integration sites will deepen our understanding of mechanisms underlying integration. Moreover, the quantity and biological activity of integration sites may reflect the DNA damage within affected cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 111 publications
(231 reference statements)
1
7
0
Order By: Relevance
“…One approach to address potential bias is digital droplet PCR (ddPCR) and it is reassuring to see consistent observations between our study and that of Prakash et al, who used this method [ 24 ]. Several studies have identified chimeric human-viral transcripts where HBV integrates in the proximity of promoters or inter/intra- genic region (reviewed in [ 45 ]). Our PCR approach cannot discriminate between chimeric 5’-human-HBV-3’ RNA transcripts and authentic viral RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to address potential bias is digital droplet PCR (ddPCR) and it is reassuring to see consistent observations between our study and that of Prakash et al, who used this method [ 24 ]. Several studies have identified chimeric human-viral transcripts where HBV integrates in the proximity of promoters or inter/intra- genic region (reviewed in [ 45 ]). Our PCR approach cannot discriminate between chimeric 5’-human-HBV-3’ RNA transcripts and authentic viral RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, transcripts detected by RT-Alu-PCR targeting the X region would have a relatively higher level than those detected by targeting the S region. The inconsistent result observed by Erken et al (figure 2 of their study) could be explained by the instability and inward shortening of the integrated HBV fragments along with disease progression, [2,3] making it impossible to detect the 3′ truncated chimeric S and X transcripts. Indeed, levels of integrated HBV DNA containing open reading frame (ORF) X (but not S) in the chronic HBV-infected individuals (ChI) group were lower than those in the HBeAg-negative chronic hepatitis B (CH) group (figure 4A,D of their study).…”
mentioning
confidence: 73%
“…Promising data have also emerged on the utility of circulating HBV-human chimeric DNA, resulting from HBV-DNA integration events, as a useful non-invasive biomarker for early identification of HCC development and its recurrence (Li et al, 2018;Liu et al, 2021;Zhang D. et al, 2021; Table 1). In 2019, a study demonstrated, for the first time, the presence of cell-free chimeric HBV-human DNA from blood samples of 20 patients with chronic HBV infection.…”
Section: Hepatitis B Virus Integration As a Diagnostic Biomarker Of H...mentioning
confidence: 99%